PENERJEMAHAN NOMINA BAHASA INGGRIS PADA NOVEL THE PENDERWICKS KARYA JEANNE BIRDSALL KE DALAM BAHASA INDONESIA - TERWELINE TAPILATU (DINAMIS, 2016)
This research, which is a qualitative one, aims at describing how nouns in the novel The Penderwicks are translated into Indonesian and how the procedures used in translating the nouns affect the equivalence between the source and target texts as well as the acceptability and naturalness of the target text. The data were collected from two documents, i.e. the English novel The Penderwicks: a Summer Tale of Four Sisters, Two Rabbits, and a Very Interesting Boy by Jeanne Birdsall and its translation ‘Keluarga Penderwick: Kisah Musim Panas Empat Kakak-Beradik Perempuan, Dua Kelinci, dan Seorang Anak Laki-Laki yang Menarik’ in Indonesian, and were analised using the content analysis method. The findings show that the English nouns were translated into different forms and meanings by using eight procedures i.e. shifts, modulation, contextual conditioning, naturalisation, transference (borrowing), translation by omission, translation by paraphrase using a related word, and translation by paraphrase using unrelated words. The purposes for applying these various procedures are mainly to bridge the differences between both languages including their cultures, produce natural equivalents in the target text, adjust the context of utterance in the source text into the target one, overcome the lack of vocabulary in the target text, produce effective sentences, and clarify the source text meaning. The use of some of these procedures has resulted in the shift of meaning but there is no significant distortion of meaning. The translation text is generally intelligible, acceptable, natural and considered appropriate for its intended readers, i.e. children.